A New Triple-Band Four-Way Filtering Power Divider With Highly Improved Performance - Li, Yibing; Zhou, Xin; Sun, Xiaohang; Gu, Xiaojun; Xu, Bin; Zhang, Xinde; Ping, Kang (Frontiers in Physics, 2022)
This letter presents a new triple-band four-way filtering power divider (FPD) with greatly improved frequency selectivity and in-band isolation. By elaborately developing a multi-port multi-mode topology between four identical multi-mode resonators and feedlines, a triple-band four-way FPD is attained. In order to validate the feasibility of the proposal, one prototype is designed, fabricated, and measured. Both the simulated and measured results of the designed FPD are provided with a good agreement. Results indicate that this triple-band four-way FPD exhibits not only sharp selective filtering performance, but also satisfactory port-to-port isolations.